NATIONAL HEALTH INSURANCE AND CATASTROPHIC HEALTH EXPENDITURE: A COMPLEMENTARY LOG-LOG APPROACH ON YOGYAKARTA’S INCIDENCE 2022 - Erdi Fakhriandi; Wahyuni Andriana Sofa (Barekeng)
National Health Insurance (JKN) aims to provide health care benefits to meet people's basic health needs. However, despite the high JKN coverage in D.I.Yogyakarta Province, catastrophic health expenditure events remain high. The study examines the implementation of National Health Insurance (JKN) in D.I.Yogyakarta Province and its effectiveness in reducing devastating health expenditures in 2022. Using the Complementary Log-log approach on the 2022 National Social and Economic Survey data, the research findings reveal that the implementation of JKN has been successful, and the ownership of JKN positively affects the reduction of catastrophic health expenditure. The study also shows that the education level of household members and household size have positive effects on reducing the incidence of catastrophic health expenditures. However, the presence of babies or the elderly, household economic status, and inpatient status could increase the risk of having catastrophic health expenditures. The study highlights the need for attention to be given to implementing JKN in D.I.Yogyakarta Province and other variables to achieve universal health coverage and reduce catastrophic health expenditure.